Volatiles Emitted from Maize Ears Simultaneously Infected with Two Fusarium Species Mirror the Most Competitive Fungal Pathogen - Sherif, Mohammed; Becker, Eva-Maria; Herrfurth, Cornelia; Feussner, Ivo; Karlovsky, Petr; Splivallo, Richard (Frontiers in Plant Science, 2016)
Along with barley and rice, maize provides staple food for more than half of the world population. Maize ears are regularly infected with fungal pathogens of the Fusarium genus, which, besides reducing yield, also taint grains with toxic metabolites. In an earlier work, we have shown that maize ears infection with single Fusarium strains was detectable through volatile sensing. In nature, infection most commonly occurs with more than a single fungal strain; hence we tested how the interactions of two strains would modulate volatile emission from infected ears. For this purpose, ears of a hybrid and a dwarf maize variety were simultaneously infected with different strains of F. graminearums and F. verticillioides and, the resulting volatile profiles were compared to the ones of ears infected with single strains. Disease severity, fungal biomass and the concentration of an oxylipin 9-hydroxy octadecadienoic acid, a signaling molecule involved in plant defense, were monitored and correlated to volatile profiles. Our results demonstrate that in simultaneous infections of hybrid and dwarf maize, the most competitive fungal strains had the largest influence on the volatile profile of infected ears. In both concurrent and single inoculations, volatile profiles reflected disease severity. Additionally, the data further indicate that dwarf maize and hybrid maize might emit common (i.e. sesquiterpenoids) and specific markers upon fungal infection. Overall this suggests that volatile profiles might be a good proxy for disease severity regardless of the fungal competition taking place in maize ears. With the appropriate sensitivity and reliability, volatile sensing thus appears as a promising tool for detecting fungal infection of maize ears under field conditions.